Kontekstualisasi surat al-Kafiru Kontekstualisasi surat al-Kafirun di tengan pluralisme : (pendekatan ma'na cum maghza) - Achmad Soib (Tanzil: Jurnal Studi Al-Quran, 2022)
This research aims to discuss the interpretation of Surah Al-Kāfirūn that is contextualized in a pluralistic society. Motivated by increase in cases of conflict in the name of religion caused by intolerance, radicals, even discriminatory and sentimental actions against other groups. This article on the contextualization of Surah Al-Kāfirūn amid in religious pluralism with a ma‘na cum maghzā approach aims to provide an understanding and explanation of moderation in religion, such as: The values of tolerance inter-religious, as well as infidels freedom should be guaranteed, both individually and in groups, to practice in worship or social-religious rites according to their respective beliefs without disturbing and hurting each other, either by word or deed. Through the ma‘na cum maghzā approach, the contextualization of Q.S Al-Kāfirūn provides more explanations to be practiced in a pluralistic society. The author hypothesizes that every claim to the truth of his religion is still needed as a form of affirmation of the identity of his belief, but this is not allowed in the aspect of communication between extra-religious, that inter-religious people can live in harmony and peace. Furthermore, this article tries to formulate the values of tolerance in Q.S Al-Kāfirūn or eliminate religious conflicts in a plural society and radicalism by using the theory of ma‘na cum maghzā.